Bilateral internal mammary artery bypass grafting: long-term clinical benefits in a series of 1000 patients. Issue 12 (20th March 2013) - Popovic, Batric; Voillot, Damien; Maureira, Pablo; Vanhuyse, Fabrice; Agrinier, Nelly; Aliot, Etienne; Folliguet, Thierry; Villemot, Jean Pierre
Abstract : Objective: Bilateral internal mammary arteries (BIMA) remain widely underused in coronary artery bypass grafting (CABG). In this study, we aim to investigate the early and long-term outcomes of BIMA grafts in isolated CABGs. Design: Single-centre retrospective observational study. Setting: University Hospital, Nancy. Patients: 1000 consecutive patients undergoing elective, isolated, primary, multiple CABGs using BIMA grafts and supplemental venous grafts for multi-vessel coronary disease. Main outcome measures: In-hospital mortality and major morbidity, and long-term all-cause mortality. Results: Mean age of the overall population was 60±15 years. A left ventricular ejection fraction (LVEF) ≤45% was found in 28% of the patients and 27.1% of the patients were diabetics. Comorbidities were represented by chronic renal failure, chronic obstructive pulmonary disease and peripheral artery disease in 11, 11.7 and 27.3% of the cases, respectively. The in-hospital mortality rate was 2.8%. Early postoperative morbidity included myocardial infarction (2.2%), stroke (0.9%), mesenteric ischaemia (0.7%) and mediastinitis (2.2%). The Kaplan–Meier 8-year survival rates for patients less than 65 and between 65 and 74 years of age were 88% and 66%, respectively (p<0.01). Multiple regression analysis showed that patients' age 65 years or greater at baseline (OR 2.3; 95% CI 1.3 to 4, p<0.001), acute coronary syndrome (OR 1.9; 95% CI 1.1 to 3.4, p=0.02), chronic renal failure (OR 2.7; 95% CI 1.4 to 5.2, p<0.001), peripheral artery disease (OR 3.1; 95% CI 1.8 to 5.5, p<0.001) and LVEF ≤45% (OR 2.6; 95% CI 1.4 to 4.5, p<0.001) were independent predictors of long-term cardiovascular mortality. Conclusions: Our longitudinal analysis presents encouraging data concerning operative risk of BIMA grafting and provides excellent long-term survival in appropriately selected patients.